2010
DOI: 10.1590/s0004-27302010000300010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of metformin, gliclazide MR and rosiglitazone in monotherapy and in combination for type 2 diabetes

Abstract: Objective: To compare the efficacy and tolerability of metformin, rosiglitazone and gliclazide MR as monotherapy and in combination in the treatment of type 2 diabetes. Subjects and methods: 250 patients treated with oral antidiabetic agents for at least 24 weeks in monotherapy or in combination therapy were included in this retrospective study. Results: As monotherapy the reduction of fasting plasma glucose (FPG), postprandial glycemia (PPG) and HbA1c was similar with the three drugs after 24 weeks. Among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Patients with a BMI≥40kg/m 2 are considered to be severely obese and have an even greater risk of presenting comorbidities related to excessive weight 2 . Among the cases of diabetes, 80 to 90% are type II and usually affect obese patients and over 40 years of age 3 . More than 80% of these patients also have metabolic syndrome (dyslipidemia, abdominal obesity, impaired glucose tolerance or diabetes and hypertension), leading to a high cardiovascular risk 3,4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with a BMI≥40kg/m 2 are considered to be severely obese and have an even greater risk of presenting comorbidities related to excessive weight 2 . Among the cases of diabetes, 80 to 90% are type II and usually affect obese patients and over 40 years of age 3 . More than 80% of these patients also have metabolic syndrome (dyslipidemia, abdominal obesity, impaired glucose tolerance or diabetes and hypertension), leading to a high cardiovascular risk 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the cases of diabetes, 80 to 90% are type II and usually affect obese patients and over 40 years of age 3 . More than 80% of these patients also have metabolic syndrome (dyslipidemia, abdominal obesity, impaired glucose tolerance or diabetes and hypertension), leading to a high cardiovascular risk 3,4 . In addition, there is an association between obesity and the onset of various types of cancer 5 .…”
Section: Introductionmentioning
confidence: 99%
“…SUs have demonstrated significant reductions in HbA1c and fasting plasma glucose (FPG) from baseline when administered as monotherapy [14][15][16], as well as dual therapy in combination with metformin, an alpha-glucosidase inhibitor (AGI), a GLP-1RA or basal insulin [15,[17][18][19], and as triple therapy in combination with metformin and either a DPP-4 inhibitor or SGLT2 inhibitor [20,21]. With regard to triple therapy, the STRATEGY study was a unique study of SUs, metformin and a DPP-4 inhibitor conducted in China [21].…”
Section: The Role Of Sulfonylurea-based Combination Therapy In This Pmentioning
confidence: 99%
“…The percentage of patients on target (i.e., HbA1c B 7%) ranged from 46.7 to 72% with SU monotherapy and approximately 40% with SUbased dual and triple therapies [15,16,[19][20][21][22]. Furthermore, results of the EasyDIA study revealed that uptitration of the SU dosage (between 30 and 120 mg per day) was associated with improved glycemic control, with dose-related significant improvements from baseline (all p \ 0.001) observed in mean levels of HbA1c and FPG after 6 months of gliclazide modified release (MR) [23].…”
Section: The Role Of Sulfonylurea-based Combination Therapy In This Pmentioning
confidence: 99%
“…The three main options among oral glucose-lowering drugs are metformin, sulphonylureas and thiazolidinediones (TZDs) (7)(8)(9)(10). More recently, DPP-4 inhibitors, such as vildagliptin, sitagliptin and saxagliptin, became commercially available (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%